КЕРУВАННЯ ПАРАЛЕЛЬНИМ АКТИВНИМ ФІЛЬТРОМ ТРИФАЗНОЇ ТРИПРОВІДНОЇ МЕРЕЖІ В СИСТЕМІ КООРДИНАТ МЕТОДУ ДВОХ ВАТМЕТРІВ - Артеменко, М.Ю.; Кутафін, Ю.В.; Михальський, В.М.; Поліщук, С.Й.; Чопик, В.В.; Шаповал, І.А. (Інститут електродинаміки НАН України, Київ, 2021)
A combined control system for a shunt active filter in the coordinate system of the two-wattmeters method has been proposed, which, depending on the conditions of use, implements one of the four active filtration strategies, optimal according to a certain quality indicator. The most promising is the proposed integral strategy for active filtration control with the reference vector of line voltages of direct sequence, which provides symmetric sinusoidal currents of the network and the minimum pulsation of power consumption for the almost identical energy-saving effect as the concept of S. Fryze. New formulas for calculating the energy-saving effect and pulsations of the instantaneous power in a three-phase system of power in the case of the formation of an active current in the transmission line in the conditions of asymmetry of loading voltage and linear asymmetric load have been developed. Simulation studies have confirmed the adequacy of the proposed strategies and calculations. References 15, figures 5, tables 2.